The Playful Desire of Gandana Ensemble in the Deliberation of Sounds - Listiowati, Nensi; Hariyanto, Gabriella Charis; Soukotta, Ferdy Karel (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2024)
Gandana is an experimental sound ensemble formed by Jogja Disability Art with instrument maker Nanang Garuda. Gandana together with the instrument maker has the concept of sound deliberation. Sound deliberation is a responsive tone-by-tone improvisation that is played spontaneously. Inclusive development in various sectors, including arts in Indonesia, accommodates the artistic expression of artists with disabilities, such as Suluh Sumurup Art Fest 2023 and Biennale 2023. Various stages of experimentation were passed by Gandana and the instrument maker as a forum for creative sound deliberation. This article shows that sound deliberation is Gandana’s desire to play. The relevance between social identity and play desires is used to get recognition from other communities. Data was obtained through literature study, interviews, documentation, and observations at two locations, Suluh Sumurup Art Fest and Jogja Biennale 2023 Interview was conducted at Rumah Museum Garuda with six informants, including Nanang Garuda as the instrument maker and Gandana’s members. The data is divided into two categories, primary and secondary. This research applies inductive logic, where the exploration began through field studies, interviews, and observations. The data then got into the analysis stage to produce a systematic description of the findings. This research reveals that sound deliberation is a playful desire used by Gandana to unite the sense and soul of others, as well as build meditative nuances through the repetition of sounds.